Paediatric major trauma in the setting of the Irish trauma network. Issue 8 (August 2021) - McAleese, Timothy; Brent, Louise; O'Toole, Patrick; Synnott, Keith; Quinn, Nuala; Deasy, Conor; Sheehan, Eoin
Highlights: The construction of a tertiary children's hospital and strategic planning of a paediatric trauma network will align Ireland with the international standard of trauma care. The most frequent mechanisms of trauma were falls <2 m (36.8%) followed by RTAs (24.3%). Head injuries make up 26% of traumatic injuries in Irish children <16 years as opposed to 18% in adults. Paediatric major trauma patients were more than twice as likely to require inter-hospital transfer compared to adult major trauma patients (46% vs 20%). Developing orthopaedic, general surgical and anaesthetic services in regional Trauma Units (TU) will be crucial for the efficient operation of the inclusive trauma network. Abstract: Background: The construction of a new tertiary children's hospital and reconfiguration of its two satellite centres will become the Irish epicentre for all paediatric care including paediatric trauma. Ireland is also currently establishing a national trauma network although further planning of how to manage paediatric trauma in the context of this system is required. This research defines the unknown epidemiology of paediatric major trauma in Ireland to assist strategic planning of a future paediatric major trauma network. Methods: Data from 1068 paediatric trauma cases was extracted from a longitudinal series of annual cross-sectional studies collected by the Trauma Audit and Research Network (TARN). All paediatric patients between the ages of 0-16 suffering AIS ≥2 injuries in Ireland between 2014-2018 were included. Demographics, injury patterns, hospital care processes and outcomes were analysed. Results: Children were most commonly injured at home (45.1%) or in public places/roads (40.1%). The most frequent mechanisms of trauma were falls <2 m (36.8%) followed by RTAs (24.3%). Limb injuries followed by head injuries were the most often injured body parts. The proportion of head injuries in those aged <1 year is double that of any other age group. Only 21% of patients present directly to a children's hospital and 46% require transfer. Consultant-led emergency care is currently delivered to 41.5% of paediatric major trauma patients, there were 555 (48.2%) patients who required operative intervention and 22.8% who required critical care admission. A significant number of children in Ireland aged 1-5 years die from asphyxia/drowning. The overall mortality rate was 3.8% and was significantly associated with the presence of head injuries ( p  < 0.001). Conclusion: Paediatric Trauma represents a significant childhood burden of mortality and morbidity in Ireland. There are currently several sub-optimal elements of paediatric trauma service delivery that will benefit from the establishment of a trauma network. This research will help guide prevention strategy, policy-making and workforce planning during the establishment of an Irish paediatric trauma network and will act as a benchmark for future comparison studies after the network is implemented.